The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1159/000319890
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Adjuvant Therapy after Transoral Robotic Resection for Oropharyngeal Carcinomas: Rationale and Current Treatment Approach

Abstract: The advancement of transoral surgical techniques for the management of oropharyngeal carcinomas has raised questions about how adjuvant therapy can best be integrated. Some of these questions have come from the application of established oncologic principles of adjuvant therapy, and some are unique to the evolving experience with transoral surgery and in particular with the recent advancement of robotic surgery. It is important for all members of the multidisciplinary treatment team to have a clear understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…Surgery, followed by a shortened course of radiation therapy without chemotherapy, may have fewer late toxic effects than definitive chemoradiotherapy. [33][34][35] However, the treatment decision is partly dependent on accurate pretreatment detection of ECS. Patients with ECS identified after TORS and neck dissection will still require adjuvant chemotherapy and near full-level radiation therapy, attenuating the potential advantages of TORS.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery, followed by a shortened course of radiation therapy without chemotherapy, may have fewer late toxic effects than definitive chemoradiotherapy. [33][34][35] However, the treatment decision is partly dependent on accurate pretreatment detection of ECS. Patients with ECS identified after TORS and neck dissection will still require adjuvant chemotherapy and near full-level radiation therapy, attenuating the potential advantages of TORS.…”
Section: Discussionmentioning
confidence: 99%
“…17 Can we safely exclude the primary site from our radiation field in certain situations, as has been suggested by Quon et al? 18 We have previously reported on 69 patients with oropharyngeal cancer that were treated with TLM alone. 19 Forty-four of the 69 patients were stage III or IV and there were only 3 local recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of relative indications for adjuvant treatment, the risks and benefits of treatment vs observation are discussed in detail with the patient. Quon et al 8 have previously described the rationale and approach for postoperative irradiation following TORS.…”
Section: Methodsmentioning
confidence: 99%